Perbedaan Tingkat Pengetahuan tentang Resiko Kehamilan Usia Dini terhadap Kejadian Kehamilan Usia Dini di Puskesmas Wagir Kabupaten Malang - Ariani, Novida; Agustin, Danik; Irmawati, Oktin (LPPM Institut Teknologi Dan Kesehatan Aspirasi, 2024)
Early pregnancy is a pregnancy where the mother's age is less than 20 years, it is closely related to the high risk of pregnancy. One of the factors causing the increasing incidence of early pregnancy is the lack of knowledge about the dangers of early pregnancy among adolescents. A low level of knowledge about pregnancy can influence adolescents in behaving negatively so that it can cause pregnancy in adolescents. This study is to determine the different levels of knowledge about the risk of early pregnancy on the incidence of early pregnancy in the Wagir Health Center of Malang Regency. The research design used in this study is quantitative with a case control approach. This study included 60 respondents using the purposive sampling method. The results of the study showed that the level of knowledge in pregnant women aged >20 years was better than the level of knowledge of pregnant women aged <20 years. The results of the Chi-Square test obtained p = 0.000 < 0.05 which showed that H0 was rejected. This means that there is a significant difference in the level of knowledge between pregnant women aged >20 years and pregnant women aged <20 years at the Wagir Health Center in Malang Regency.